Development of Technological Equipment to Laboratory Test In-situ Laser Cladding for Marine Engine Crankshaft Renovation. (2015) - Torims, Toms; Pikurs, Guntis; Ratkus, Andris; Logins, Andris; Vilcans, Janis; Sklariks, Stepans
Abstract: This article presents the development of novel technological equipment for laboratory testing marine diesel engine crankshaft renovation using an in-situ laser cladding device. It outlines the technology and method devised to perform crankpin journal renovation operations directly in the engine housing, without removing the crankshaft from the engine. Firstly it describes marine crankshafts and the common faults of their main and crankpin bearings. There follows an analysis of conventional crankshaft repair methods, along with their limitations. The principles of laser cladding nozzles are then described, outlining the benefits of laser cladding technology for in-situ marine crankshaft repairs. The paper goes on to assess previous studies in field and the laser cladding repair solutions currently proposed for marine crankshafts. It also indicates the view taken by Classification Societies towards laser-cladding crankshaft repairs. The development of the in-situ prototype equipment is detailed, along with full-size prototype design steps, accompanied by the relevant analysis and considerations. In addition, appropriate calculations for the laboratory test device are given. The technological process and method described in this article are an innovative application of additive manufacturing technology to the crucial requirements of modern, ship-repair enterprises. In-situ crankshaft laser cladding is a promising technology with good financial prospects.